1987
DOI: 10.1073/pnas.84.9.2620
|View full text |Cite
|
Sign up to set email alerts
|

Effects of DNA supercoiling on the topological properties of nucleosomes.

Abstract: In the nucleosome core particle, at least 145 base pairs of DNA are bound to the histone octamer in a superhelical conformation. We have asked what effect the presence of these particles has on the ability of DNA gyrase to supercoil DNA. Synthetic minichromosomes, constructed by reconstituting complexes of core histones with the closed circular plasmid pBR322, were treated with various amounts of DNA gyrase. We have found that the maximum level of supercoiling that is attainable is nearly identical for protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…Recent data on DNA minicircles showed the same maximum value of -oGyr [45]. In addition, it has been shown that oGYr does not change with increasing amount of gyrase added (starting from a specified value) [44]. This conclusion is supported by our experiments.…”
Section: Resultssupporting
confidence: 81%
“…Recent data on DNA minicircles showed the same maximum value of -oGyr [45]. In addition, it has been shown that oGYr does not change with increasing amount of gyrase added (starting from a specified value) [44]. This conclusion is supported by our experiments.…”
Section: Resultssupporting
confidence: 81%
“…(B) Supercoiling of plasmid DNA isolated from ES114 or topA mutants was assayed by electrophoresis through 0.8% agarose containing 20 g/ml chloroquine. DNA that is less negatively supercoiled prior to loading will migrate more rapidly at this concentration of chloroquine (29). Laddering on the gel is indicative of topoisomers of the same plasmid that differ by one linking number.…”
Section: Discussionmentioning
confidence: 99%
“…4b): ∆Lk ~ -1 obtained in higher salt against ∆Lk ~ -0.8 in B 0 (also favoring entry-exit DNA repulsion) [Interestingly, a similar ~+0.2 shift in ∆Lk was also measured in the minicircle system with acetylated mononucleosomes in phosphate, a buffer which further destabilizes histone tails/DNA interactions 9 .] ii) The property of reconstituted minichromosomes to withstand as much negative supercoiling (σ~-0.1) as the corresponding naked DNA upon treatment with DNA gyrase 35 , i.e. the nucleosome apparent "transparency" to that enzyme in spite of the trapping of most DNA in the nucleosome cores, must result from the shift of all nucleosomes to the negative state 9 , rather than from a forced undertwisting of the DNA on the histone surface 34 .…”
Section: Nucleosome Transitions and Chromatin Topologymentioning
confidence: 99%